IMPACT OF REGIONAL TRANSFORMATIONS ON ALGERIAN FOREIGN POLICY DIRECTIONS - Prof. Dr. Ömer Göksel İşyar; Yakoub Sid (American Journals Publishing, 2022)
The Arab region, particularly North Africa (Egypt, Libya and Tunisia), has undergone transformations that have led to the overthrow of its governing regimes. During these shifts, Algeria has adopted the option of caution and anticipation towards the People's Movement as it deals sensitively with all things that call for sudden or chaotic change; Against the backdrop of what it experienced during the internal crisis known as the Black Mankind, Algeria was afraid of the transmission of the uprisings.
Keywords: North Africa, Transformations, Algerian Foreign Policy, Arab Spring, Cooperation.